Upper Large Deviations for Mixing Random Sequence (Communications in Mathematical Research, 2021)
In this article, we prove upper large deviations for the empirical measuregenerated by stationary mixing random sequence under some suitable assumptionsand upper large deviations for the mixing random sequence.